Ultrastructural study of the relation of the neural gland-ganglionic complex to ovarian development in the ascidian, Styela partita (Stimpson,1852) - Kh, Mohie (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Abstract: The ultrastructure of the neural complex and the stages of oocyte maturation during oogenesis were investigated in the ascidian Styela partita collected from the intertidal zone of the Mediterranean Sea, Alexandria. The neural complex can be differentiated into cerebral ganglion, neural gland and dorsal strand . The cerebral ganglion is divided into three parts as cerebral cortex, medullary layer and transitional zone. The ganglion is surrounded by blood sinuses and covered with a thin fibrous sheath through which many nerve fibres run. The ganglion is composed of a cellular cortex and a fibrous medulla. The cortex is multilayered of large and small neurons. Some neurons are also scattered within the medulla. Many neurons are monopolar, and some are bi- or multipolar and some are mononucleated and others are binucleated.. The cytoplasm of the large neurons is dense with extensive rough endoplasmic reticulum, free ribosomes, mitochondria, one or more Golgi complexes and many clear or dense vesicular structures. Some neurons send their processes directly into the lumen of the sinuses. The medulla is composed of loosely arranged nerve fibres without cellular wrappings. The medullary fibres contain vesicles and granules of various sizes and microtubules. At the anterior and posterior ends of the ganglion, the medullary fibres are assembled into thick peripheral nerve fibre bundles. The peripheral nerve fibres are enveloped and subdivided by fibrous structures. Synapses are found in the medulla, in the cortex, and between the peripheral nerve fibres. The presence of neurons and axodendritic synapses in the peripheral nerve fibres is consistent with a diffuse organization of the nervous system of the ascidians. The neural gland is composed of glandular lobules, closely apposing at ventral side of the cerebral ganglion. The epithelial wall of the gland showed three morphological forms. The gland cells are polygonal and granulated. A dorsal strand extends from the neural gland and terminates at the vicinity of the gonad. The number of neurosecretory cells in the cerebral ganglion and the glandular secretion increase rapidly while oocyte development proceeds from previtellogenesis to vitellogenesis and decreases markedly after reproductive season. The oogenetic part of the germinal epithelium contains oocytes at two different stages, the dark and clear cells. The smaller oocyte contains synaptonemal complexes. The larger oocyte in the initial phase of growth has a conspicuous nucleolus, electron-dense materials and some mitochondria close to the nuclear envelope. The early follicular oocyte just after migration from the germinal epithelium retains most of cytological features of the larger oocyte. The reproductive cycle can be grouped into the following successive stages in the ovary: growth (February to June), vitellogenesis (April to September), mature (July to December), spent (November to February), and recovery (December to April). The vitellogenic oocyteÂ  consists of an association between a single fenestrated endoplasmic reticulum, cisterna and one or a few smooth vesicles containing a dense core facing the cisterna itself. The latter is smooth and perforated by numerous small pores (about 30 nm in diameter) in the area of association; towards the periphery, it extends into several branches with ribosomes bound to their membranes. In the vesicles, fibrillar material radiates from the dense core and is sometimes organized into a long, dense lamina. The membranes of both cisterna and vesicles appear to be coupled, but are in fact separated by a constant narrow space occupied by short densities. Vitellogenesis occured by way of endogeous autosynthesis and exogenous heterosynthesis: The former process involves a combined activities of the Golgi complex, mitochondria, and rough endoplasmic reticulum. The latter involves endocytotic incorporation of extraovarian precursors into the basal region of the early vitellogenic oocytes prior to the formation of vitelline envelope. The follicle cells and test cells appear to play an integral role in vitellogenesis and oocyte degeneration, functioning in phagocytosis and digestion of products originating from the degenerated oocytes. Follicle cells might have a lysosomal system for breakdown and might resorb phagosomes in the cytoplasm for nutrient storage during oocyte degeneration.